Biologically derived copper oxide-based nanocatalyst using Moringa oleifera leaves and its applications in hydrolytic enzymes and biohydrogen production. (May 2023) - Srivastava, Neha; Singh, Rajeev; Ahmad, Irfan; Asiri, Mohammed; Tripathi, Subhash C.; Rai, Ashutosh Kumar; Mishra, P.K.; Gupta, Vijai Kumar
Graphical abstract: Highlights: Phytofabrication of copper oxide based nanocatalyst using moringa leaves. Enhanced co-cultured and co-fermentative enzymes via nanocatalyst. Biohydrogen using rice husk hydrolyzate under influence of nanocatalyst. Approach is significant from the standpoint of waste management and bioenergy production. Abstract: Due to the limited availability of fossil fuels, pollution causing serious environmental issues, and their continuously rising price, the development of low-cost efficient enzymes and their implementation in biomass-based bioenergy industries are highly demanded. In the present work, phytogenic fabrication of copper oxide based nanocatalyst has been performed using moringa leaves and has been characterized using different techniques. Herein, the impact of different dosages of as-prepared nanocatalyst on fungal co-cultured cellulolytic enzyme production under co-substrate fermentation using wheat straw and sugarcane bagasse in 4:2 ratios in solid state fermentation (SSF) has been investigated. An optimal concentration of 25 ppm of nanocatalyst influenced the production of 32 IU/gds of enzyme, which showed thermal stability at 70 °C for 15 h. Additionally, enzymatic bioconversion of rice husk at 70 °C librated 41 g/L of total reducing sugars, which led to the production of 2390 mL/L of cumulative H2 in 120 h.